Jamming and percolation of parallel squares in single-cluster growth model - Kriuchevskyi, I.A.; Bulavin, L.A.; Tarasevich, Yu.Yu.; Lebovka, N.I. (Condensed Matter Physics, 2014)
This work studies the jamming and percolation of parallel squares in a single-cluster growth model. The Leath-Alexandrowicz method was used to grow a cluster from an active seed site. The sites of a square lattice were occupied by addition of the equal size k x k squares (E-problem) or a mixture of k x k and m x m (m ≤ k) squares (M-problem). The larger k x k squares were assumed to be active (conductive) and the smaller m x m squares were assumed to be blocked (non-conductive). For equal size k x k squares (E-problem) the value of pj = 0.638 ± 0.001 was obtained for the jamming concentration in the limit of k →∞. This value was noticeably larger than that previously reported for a random sequential adsorption model, pj = 0.564 ± 0.002. It was observed that the value of percolation threshold pc (i.e., the ratio of the area of active k x k squares and the total area of k x k squares in the percolation point) increased with an increase of k. For mixture of k x k and m x m squares (M-problem), the value of pc noticeably increased with an increase of k at a fixed value of m and approached 1 at k ≥ 10 m. This reflects that percolation of larger active squares in M-problem can be effectively suppressed in the presence of smaller blocked squares. В роботi вивчено явища джамiнгу i перколяцiї паралельних квадратiв для однокластерної моделi росту. Для росту кластеру з активного зародку використовувався метод Лiса-Александровича. Вузли квадратної ґратки займалися додаванням однакових k ×k квадратiв (E-задача) або сумiшi k ×k i m ×m (m É k) квадратiв (M-задача). Припускалося, що бiльшi k × k областi були активними (провiдними), а меншi були заблокованими (непровiдними). Для k ×k квадратiв однакового розмiру (E-задача) за умови k → ∞ було отримано таке значення концентрацiї джамiнгу p j = 0.638±0.001 . Це значення було iстотно меншим за отримане ранiше для моделi випадкової послiдовної адсорбцiї: p j = 0.564±0.002. Було показано, що величина перколяцiйного порогу pc (тобто вiдношення площi активних k ×k квадратiв до загальної площi осаджених k × k квадратiв в перколяцiйнiй точцi) зростала при збiльшеннi k. Для сумiшi k × k i m × m квадратiв (M-задача) величина pc сильно зростала при збiльшеннi k при фiксованому значеннi m та наближалась до 1 приk Ê 10m. Це пов’язано з тим, що перколяцiя бiльших активних квадратiв для M-задачi може ефективно пригнiчуватися за наявностi невеликої кiлькостi малих заблокованих квадратiв.